Probiotics and Functional Gastrointestinal Disorders in Pediatric Age: A Narrative Review - Capozza, Manuela; Laforgia, Nicola; Rizzo, Valentina; Salvatore, Silvia; Guandalini, Stefano; Baldassarre, Mariella (Frontiers in Pediatrics, 2022)
Assessment and management of pain are essential components of pediatric care. Pain in pediatric ages is characterized by relevant health and socio-economic consequences due to parental concern, medicalization, and long-term physical and psychological impact in children. Pathophysiological mechanisms of nociception include several pathways in which also individual perception and gut-brain axis seem to be involved. In this narrative review, we analyze the rational and the current clinical findings of probiotic use in the management of functional gastrointestinal disorders in pediatric ages, especially in infantile colic, irritable bowel syndrome, constipation, and gastroesophageal reflux. Some specific probiotics showed a significant reduction in crying and fussing compared to placebo in breastfed infants with infantile colic, although their exact mechanism of action in this disorder remains poorly understood. Regarding irritable bowel syndrome, a limited number of studies showed that specific strains of probiotics can improve abdominal pain/discomfort and bloating/gassiness in pediatric ages, but data are still inconclusive. Moreover, some strains may reduce the passage of hard stools, but currently there is not enough evidence to recommend probiotics in the management of functional constipation in children. In the same way, although some probiotic strains could promote gastric emptying with a potential improvement of functional symptoms of oesophagus and stomach, current evidence of efficacy is insufficient to provide any specific recommendation for the prevention and treatment of gastroesophageal reflux. We can conclude that probiotics have been proposed as part of management of pain in functional gastrointestinal disorders in pediatric ages, but mechanisms are still poor understood and evidence to guide clinical practice is currently lacking.